The impact of asean free trade area (AFTA) on the information technology (IT) industry in Malaysia - Ismail, Irzan (2003)
The trends in global IT in the new millennium are irreversible, and it is imperative that we study them and address them in a serious and concerted manner. The beginning of the new millennium marks a new era in global information technology and its management While the eighties and the nineties witnessed global business and global IT expansion, the issues in global IT have now reached a new level of interest and maturity. The introduction of the free trade area concept has somehow influenced the IT industry. As we can see globalization has now become a threat to every industry. These industries are either directly or indirectly affected by such rapid development in the world economy. IT is one area that is vital to organizations where the capability to control information win give them a competitive advantage in the business environment. Global IT management is the new paradigm of the next millennium; domestic IT and uni-national Information System (IS) are now only parts of the broader global IT, and it is absolutely essential that we view all aspects of TT and IS from the comprehensive and all-embracing lens ol global IT management and the impact of the free trade concept on the industry.